Motivasi Amerika Serikat Menjatuhkan Embargo Ekonomi Terhadap Myanmar Tahun 2007 - Anggara, Mustavidy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study used qualitative research methods that the source data is taken from books, journals, newspapers, internet, and previous research has relevant data with the title. Perspectives and levels of analysis used in this study is that the state as the main actor. By using the theory of liberalism and foreign policy analysis, will describe the direction of the object of analysis. This study will explain the factors that led the United States impose economic embargoes against Myanmar. To find out how the domestic situation in Myanmar before and after the embargo dropped by United States. As well as to see the effects on the fall of the economic embargo. Myanmar in the value of the United States has violated the human rights of the people. Myanmar which is led by a military junta, is considered refusing to uphold democratic values. This study will answer how the United States seeks to enhance the role, as well as trying to meet the economic interests of Southeast Asia region. The United States seeks to indoctrinate values of liberalism, democracy, and human rights freedom of Southeast Asia region. If a country refuses it, then it will have a great opportunity to drop in the economic embargo as happened in Myanmar. This is the strategy of the United States foreign policy to meet national interests and enhance the role of Southeast Asia region.